2011
DOI: 10.5402/2011/457204
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Cancer Protection: The Bivalent HPV Vaccine for Females

Abstract: Nearly a half a million women throughout the world develop cervical cancer every year Parkin and Bray (“Chapter 2. The burden of HPVrelated cancers,” Vaccine, vol. 24, no. 3, pp. S11–S25, 2006); 80% of these women are in countries without a quality-assured cytology screening program. It is in this setting that Cervarix could reduce the incidence of cervical cancer to about 9.5/100,000 women. New evidence indicates that this might be able to be accomplished with a single dose of Cervarix, a great advantage to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 128 publications
0
41
0
7
Order By: Relevance
“…Maximizing health care resources in the near term may indicate a shift to the use of HPV2, the bivalent HPV vaccine. It has efficacy proven for both one or two doses, despite FDA labeling for three doses, lasts at least 4 years for less than three doses, and may protect against seven oncogenic HPV infections at varying efficacies [35], [46], [47] Our study showed that two doses were highly likely to be completed on-time and more likely if provided at a vaccine-only visit than at a preventive visit.…”
Section: Discussionmentioning
confidence: 79%
“…Maximizing health care resources in the near term may indicate a shift to the use of HPV2, the bivalent HPV vaccine. It has efficacy proven for both one or two doses, despite FDA labeling for three doses, lasts at least 4 years for less than three doses, and may protect against seven oncogenic HPV infections at varying efficacies [35], [46], [47] Our study showed that two doses were highly likely to be completed on-time and more likely if provided at a vaccine-only visit than at a preventive visit.…”
Section: Discussionmentioning
confidence: 79%
“…No Brasil, a estimativa para o ano de 2014 publicada pelo Inca, válida também para 2015, apontou o CCU como o terceiro tipo de câncer mais incidente entre as mulheres, sendo 15.590 casos novos por ano, com um risco estimado de 15,33 casos a cada 100 mil mulheres [Ministério da Saúde (Brasil) (Harper & Vierthaler, 2011) mostrou uma taxa semelhante até os 30 anos, a princípio demonstrando equivalência de exposição aos fatores de risco. Entretanto, após essa idade, ocorre franca separação das curvas, mostrando uma incidência quase quatro vezes maior nas mulheres brasileiras em relação às britânicas aos 65 anos (Figura 3).…”
Section: Epidemiologia Do Ccuunclassified
“…1B), with a first peak occurring at young ages (mean, 42.56 years) followed by a relative rebound at older ages (mean, 60.84 years). This bimodal occurrence was evoked in other population positioning peaks at younger age of 30‐34 years and slightly older age of 65‐69 years 19. These high points of cervical cancer incidence are shifted 5‐15 years after an analogous bimodal age‐specific HPV‐infection prevalence described at 25 and 45 years of age,20 which may represent the time of cervical malignant transformation to take place with some specificity of each population remnant of possible genetic and cultural differences.…”
Section: Discussionmentioning
confidence: 91%